The Concordance of Physical Examination and Radiological Examination With Histopathological Findings In Breast Cancer Patients - Kharen Kharen; Hendrianto Hendrianto (International Journal of Health and Pharmaceutical (IJHP), 2025)
Breast cancer is a malignancy arising from the mammary glands and is the most common cancer found in women. The diagnosis of breast cancer is established using the triple assessment method, which involves physical examination, radiological assessment, and histopathological examination of the breast. This study aims to determine the concordance between physical and radiological examinations with histopathology, which serves as the gold standard. The study utilized an observational analytic cross-sectional design, gathering data from the medical records of breast cancer patients at Royal Prima General Hospital and Dr. Pirngadi General Hospital in Medan. Statistical testing using Chi-Square showed no significant concordance between physical examination and histopathological examination (p>0.05). The radiological examination, however, showed significant concordance but with a negative correlation, suggesting that a higher histopathological grade is associated with a lower BI-RADS level (r=-0.189; p=0.039). Radiological examination demonstrated better concordance with histopathology compared to the physical examination, but it still cannot replace the role of histopathology as the gold standard for breast cancer diagnosis.